Analisis Sanad dan Matan Hadis tentang Pendidikan Adab Peserta Didik dan Pendidik - Imadudin Abil Fida Asabily; Nanang Qosim (Lembaga Yasin AlSys, 2026)
Although moral education in Islam has received considerable attention in various studies, research specifically examining the quality of hadiths concerning the moral conduct of students and educators through an integrated analysis of the sanad and matan remains limited. This study aimed to analyze the quality of hadiths concerning the moral education of students and educators and to examine their relevance to contemporary Islamic education. This study employed a qualitative approach using library research focused on hadiths contained in the major hadith collections, particularly the Kutub al-Tis‘ah. Data were collected through documentation and analyzed using the methods of takhrij al-hadith, naqd al-sanad, and naqd al-matan. The results showed that the principal hadith narrated by ‘Ubadah ibn al-Samit through Imam Ahmad was classified as sahih li ghairihi because it was supported by corroborating chains of transmission, whereas the supporting hadith narrated by Abu Hurairah through Imam al-Tabrani was classified as da‘if because its chain contained a narrator classified as matruk. Despite their differing levels of quality, both hadiths contain fundamental educational values of respect, compassion, humility, and moral responsibility. These findings strengthen the development of the concept of ta’dib and broaden the understanding of prophetic pedagogy in the context of contemporary education. This study affirms that authentic hadiths play an important role as a normative foundation for students’ character formation. The theoretical implication of this study lies in enriching the literature on hadith tarbawi, whereas its practical implication encourages educators, curriculum developers, and Islamic educational institutions to integrate verified prophetic values and prioritize the cultivation of moral conduct before the process of knowledge transmission. This study also opens opportunities for further research on the contextual application of hadith values in digital learning environments.